Marketing Communication Strategy for Warung Makan Madun Oseng Nyak Kopsah Through the Tiktok Social Media Account @madunosengoseng in Promoting Authentic Indonesian Culinary - Aisa Setiawati; Edy Prihantoro (LPPM Stikosa - AWS, 2024)
Indonesian culinary is the result of multicultural culture spread across 38 provinces. One of the interesting Indonesian culinary delights is typical Betawi culinary delights, namely Warung Madun Oseng Nyak Kopsah, a food stall that serves typical Betawi menus and other home-cooked dishes. The stall, which was started in 1997, is now innovating by using TikTok social media as its promotional medium. This research aims to analyze the Marketing Communication Strategy through the Tiktok Account @madunosengoseng in Promoting Authentic Indonesian Culinary. This research uses Integrated Marketing Communication theory. The research method used is a qualitative descriptive method with data collection carried out by means of observation, interviews, documentation and online search. The results of this research show that the marketing communication strategy carried out through the tiktok account @madunosengoseng, with content whose theme contains eight elements of integrated marketing communication, provides information about the food menu, and also presents content that is entertaining in nature. One of the entertaining content is the appearance of the